Apprendre à affronter l’incertitude dès l’école primaire grâce à la discussion à visée philosophique - Muriel Briançon; Amanda Marty (Recherches en Éducation)
Within the framework of the complex thought and of his book Seven knowledges necessary for the education of future, Edgar Morin suggested teaching at school a fundamental knowledge: "face the uncertainties". Can the pupil learn to face the uncertainties at elementary school? As it is connected to the Unknown, can this last one become a new object of school knowledge? In our theoretical perspective of The teaching Otherness and the Aussersein meinongien, there is well a knowledge of the Unknown which deserves its place in the school learnings. Can the philosophical discussion then become the privileged device in the service of this learning? Our review of the means to face the uncertainty (bet, elaborate strategies, ‘problématisation’, philosophize and think the unknown) and of his dimensions (the indecision, the doubt, the chance, the change, the ‘problématicité’, the unknown) allow us to establish railings for interpretating the comments of 6-11-year-old pupils collected during two DVP. Our results show that the DVP allows the children to work directly their report on the (not)knowledge. Not thought zones and competence to be developed could become new stakes in learnings in the future school.